Pengaruh Pemahaman Akuntansi, Sosialisasi dan Ukuran Usaha terhadap Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM - Puspitasari, Rinanda Aprilia; Muslimin, Muslimin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of knowing the effect of understanding accounting, socialization, and business size on the preparation of MSME financial reports based on SAK-EMKM. The data used in this study is primary data where primary data is collected through questionnaires and the measurement technique used is the Likert scale technique. This research was conducted in Dukuh Pakis District. The population in this study were all MSME actors in Dukuh Pakis District, where the number of MSME actors in Dukuh Pakis District was 180 MSME actors. The sample was selected by purposive sampling technique, the sample size was 65 SMEs. Data analysis techniques consist of descriptive statistical tests, instrument tests in the form of validity, reliability and normality tests, classic assumption tests in the form of multicollinearity tests and heteroscedasticity, multiple linear regression analysis, multiple coefficient of determination (R2), f test and t test with the help of SPSS version 26 for windows. Based on the results of the study, it shows that each variable of understanding of accounting, socialization, and business size has a positive effect on the preparation of MSME financial reports based on SAK-EMKM (Y). This can mean that all the variables used can influence MSME actors in preparing MSME financial reports based on SAK-EMKM. Keywords: SAK-EMKM, Preparation of MSME Financial Statements, Accounting Understanding, Socialization, Business Size.